La situation d’enseignement-apprentissage : caractères contextuels et construits - Marc Bru; Joël Clanet (Recherches en Éducation)
The setting accounts for many conditions (social, psychological, organizational, material) in which, and with which, the teaching practices develop in their relationships to the learning behaviors. Among the dynamic dimensions characterizing the setting, we have noticed that some of them such as time management, the task in hand, interactions between student(s)/teacher and teacher/student(s) organize configurations of practices more than others do. Interactive modalities initiated by the teacher and related to some degrees of difficulty encountered by students faced with the task proposed by the teacher can, for instance, be an explanation for the degree of mastering literacy at the end of the school year. Therefore, the setting cannot be considered as the sole arena data characterizing the conditions in which the teaching/learning practices are implemented for the setting is constructed by those involved in the education and more particularly by the person who is responsible for its functioning: the teacher.